Mendukung Guru untuk Mempelajari Perdamaian: Studi Awal di Sekolah Sukma Bangsa Sigi, Sulawesi Tengah - Wibowo, Dody (SUKMA: Jurnal Pendidikan, 2022)
Using data from a teacher from Sukma Bangsa School Sigi, Central Sulawesi, Indonesia, this paper wants to provide a preliminary finding for research on supporting teachers to learn peace. This research uses a framework that states the practice of school culture contributes to teachersâ€™ professional development for peace education. The framework provides four categories of school culture practice that can support teachers in learning peace: institutional management, school environment, facilitation for learning, and relations among teachers. The data shows that those four categories of school culture practice are found in Sukma Bangsa School Sigi. However, each category has a different level of supporting the teacher in learning peace.Â